A kind of sediment-based MOFs and its preparation method and application

Preparation of base MOFs by acid treatment and template agent heating reactions, solving the problem of dredging base sludge disposal, realizing the high-value application of base sludge and the tetracycline degradation effect, reducing costs and improving reusability.

CN115888832BActive Publication Date: 2025-02-18SOUTH CHINA AGRICULTURAL UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211292183.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-21
Publication Date
2025-02-18
Estimated Expiration
2042-10-21

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively treat and resource-based dredging of bottom sludge, resulting in the treatment of bottom sludge mostly low-value treatment and lack of high-value applications.

Method used

The river bottom sludge centrifuged after acid treatment is used as raw material, combined with the template agent, and after heating reaction, the base sludge-based MOFs are prepared.

Benefits of technology

The high-value application of base sludge has been achieved. The base sludge-based MOFs have a large specific surface area and total pore volume, can effectively degrade tetracycline, and have low cost and good reusability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115888832B_ABST
    Figure CN115888832B_ABST
Patent Text Reader

Abstract

The present invention provides a sediment-based MOFs and a preparation method and application thereof. On the one hand, MOFs prepared from sediment can better solve the problem of dredged sediment resource utilization, and have greater added value than existing disposal methods such as sediment landfill, production of ceramsite, and building bricks. On the other hand, sediment-based MOFs are synthesized using sediment, which can greatly reduce costs compared to traditional chemical reagent synthesis. In addition, sediment-based MOFs have good performance in activating persulfate to degrade tetracycline. It can be seen that using sediment as a raw material to prepare corresponding environmental functional materials can realize high-value application of sediment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of water treatment, and in particular to a sediment-based MOFs and a preparation method and application thereof. Background Art

[0002] Metal-organic frameworks (MOFs) are a new type of nano-coordination polymer that has developed rapidly in the 21st century. They are crystalline materials with a specific periodic network structure formed by the self-assembly of metal cations and organic ligands, in which the metal cations are usually transition metal ions, such as Co 2+ , Cu 2+ , Mn 2+ , Zn 2+ , Fe 3+ or metal clusters, such as [Co4O] 6+ , while the linker is usually an oxygen- or nitrogen-containing ligand, such as carboxylate, imidazole, etc. From a microscopic point of view, MOFs have abundant pores, so their specific surface area is very large, and due to their special metal-organic coordination polymerization mode, their structure can be designed and regulated in a variety of ways. In addition, MOFs also have the characteristics of topological structure diversity and tailorability. Due to these excellent properties, MOFs have been widely used in catalysis, gas adsorption, separation, sensing and drug release.

[0003] Black and smelly sludge pollution has adverse effects on the ecological environment and human health. Effective sludge management is the key to winning the battle against black and smelly water bodies. In order to obtain a stable sludge treatment effect, dredging of black and smelly sludge has become the preferred method. However, how to treat and dispose of dredged sludge has become a difficult problem for the promotion and application of this method. In the prior art, the ways to utilize sludge as a resource are composting, incineration or pyrolysis, land use, backfill materials, building materials, and preparation of expanded clay, etc. The focus is on the direct treatment of sludge as a whole, which is a low-value method. According to the characteristics of each component of the sludge, the sludge is used as a raw material to prepare the corresponding environmental functional materials, which can realize the high-value application of sludge. Research in this area is currently relatively rare. Summary of the invention

[0004] The purpose of the present invention is to overcome the shortcomings and deficiencies of the prior art and to provide a method for preparing sediment-based MOFs.

[0005] Another object of the present invention is to provide sediment-based MOFs prepared by the above preparation method.

[0006] Another object of the present invention is to provide applications of the above-mentioned sediment-based MOFs.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A method for preparing sediment-based MOFs comprises the following steps:

[0009] (1) Treating the sludge with acid and centrifuging to separate the supernatant and the sediment;

[0010] (2) Adding a template to the supernatant obtained by centrifugation, heating the supernatant for reaction, purifying, washing, and drying to obtain the sediment-based MOFs.

[0011] The sludge in step (1) is river bottom sludge; preferably, the sludge mainly comprises silicon dioxide and aluminum oxide.

[0012] The components of the sludge in step (1) are 50-80% silicon dioxide and 20-50% aluminum oxide; preferably 50-70% silicon dioxide, 10-30% aluminum oxide, 5-10% ferric oxide, 2-5% calcium oxide, 1-3% potassium oxide, 0.5-2% magnesium oxide and 0.5-2% titanium oxide; further preferably 55%-65% silicon dioxide, 15-25% aluminum oxide, 7-9% ferric oxide, 3-4% calcium oxide, 2-3% potassium oxide, 1-2% magnesium oxide and 1-2% titanium oxide.

[0013] The sludge in step (1) is sludge that has passed through a 100-300 mesh sieve; preferably, sludge that has passed through a 100 mesh sieve.

[0014] The acid in step (1) is hydrochloric acid; preferably 6 mol / L hydrochloric acid.

[0015] The treatment in step (1) is performed by shaking at 30-40° C. and 100-200 r / min for 1-3 h; preferably, by shaking at 35° C. and 150 r / min for 2 h.

[0016] The centrifugal conditions in step (1) are 4000-6000 r / min, 5-20 min; preferably 5000 r / min, 10 min.

[0017] The supernatant in step (1) is also filtered using a 0.4-0.5 micron filter head, and the filter residue obtained by filtration is combined with the precipitate obtained by centrifugation; preferably, it is filtered using a 0.45 micron water filter head.

[0018] The template agent in step (2) is trimesic acid (H3BTC).

[0019] The amount of the template added in step (2) is determined by the sum of the molar mass of Al and Fe in the supernatant: the molar mass of the template = 2 to 4:2; preferably, it is determined by the molar ratio = 3:2.

[0020] The template agent in step (2) is pre-dissolved in an organic solution before being added to the supernatant; preferably, it is pre-dissolved in DMF.

[0021] The heating reaction in step (2) is carried out at 140-160° C. for 12-18 hours, preferably at 150° C. for 15 hours.

[0022] The purification described in step (2) is to remove the template by washing with N,N-dimethylformamide, ethanol and water respectively.

[0023] The drying in step (2) is vacuum drying; preferably vacuum drying at 60° C. for 12 h.

[0024] The washing in step (2) is washing with anhydrous ethanol and deionized water.

[0025] A kind of sediment-based MOFs is prepared by the above preparation method.

[0026] The application of the above-mentioned sediment-based MOFs in the treatment of organic wastewater by activating persulfate.

[0027] Compared with the prior art, the present invention has the following advantages and effects:

[0028] On the one hand, the present invention can better solve the problem of dredged sediment resource utilization, and has greater added value than existing sediment landfill, ceramsite production, building bricks and other disposal methods. On the other hand, sediment-based MOFs are synthesized using sediment, which can greatly reduce costs compared to traditional chemical reagent synthesis. In addition, sediment-based MOFs have good performance in activating persulfate to degrade tetracycline. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 It is the XRD spectrum of the product and the simulated XRD pattern of single crystal of MIL-100 (Fe) and MIL-100 (Al) standard substances.

[0030] Figure 2 These are the SEM photos, TEM photos and metal distribution diagrams of sediment-based MOFs; (a) is the SEM picture, (b) is the element component content determined by EDS, (c) is the TEM-Mapping diagram, and (d~e) are the distribution diagrams of different metal elements in MOFs.

[0031] Figure 3 This is the FT-IR spectrum of sediment-based MOFs.

[0032] Figure 4 These are the N2 adsorption-desorption isotherms and pore size distribution diagrams of sediment-based MOFs; (a) is the N2 adsorption-desorption isotherm, and (b) is the pore size distribution diagram.

[0033] Figure 5 This is the TGA weight loss curve of sediment-based MOFs.

[0034] Figure 6 This is a graph showing the degradation effect of sediment-based MOFs on tetracycline at different pH values.

[0035] Figure 7 This is a graph showing the degradation effect of sediment-based MOFs on tetracycline at different sediment-based MOFs concentrations.

[0036] Figure 8 This is a graph showing the degradation effect of sediment-based MOFs on tetracycline at different persulfate concentrations.

[0037] Fig. 9 This is a graph showing the degradation efficiency of tetracycline by sediment-based MOFs in a recycling experiment. DETAILED DESCRIPTION

[0038] The present invention is further described in detail below in conjunction with embodiments and drawings, but the embodiments of the present invention are not limited thereto.

[0039] If no specific experimental conditions are specified in the following embodiments, conventional experimental conditions or experimental conditions recommended by the reagent company are generally followed. The materials and reagents used, unless otherwise specified, are all reagents and materials obtained from commercial sources.

[0040] Example 1 Synthesis of sediment-based MOFs

[0041] The sediment samples were collected from a river in Jiangmen, and the contents of their components were determined by X-ray fluorescence spectroscopy (XRF). The results are shown in Table 1.

[0042] Table 1 Composition of sediment

[0043]

[0044] The sludge passed through a 100-mesh sieve was mixed with deionized water and a certain concentration of HCl in a specific proportion, and oscillated at 35°C and 150 r / min for 2 h. The mixture was centrifuged at 5000 rpm for 10 min, and the supernatant was filtered with a 0.45-μm water filter. The filtrate was collected and stored for the preparation of sludge-based MOFs.

[0045] Take 1000ml of the sludge filtrate obtained in the leaching step, and the Fe and Al contents are measured to be 628mmol (28.55g) in total. According to the metal ion content in the filtrate, with Fe and Al as the central atoms, trimesic acid (H3BTC) as the template, and the molar ratio of metal ions: trimesic acid = 3:2, take 87.979g trimesic acid, add it to 1319.69mL N, N-dimethylformamide (DMF) and stir continuously until it is completely dissolved. Then take the above solution and add it to 1000ml of the leaching solution and mix it evenly, then put it into a stainless steel reactor lined with polytetrafluoroethylene, react at 150℃ for 15h, and filter the product after natural cooling. The filtrate is washed with N, N-dimethylformamide, ethanol and water to remove the template, and finally filter it and vacuum dry it at 60℃ for 12 hours to obtain the sludge-based MOFs.

[0046] Example 2 Characterization of sediment-based MOFs

[0047] The sediment-based MOFs obtained in Example 1 were characterized by scanning electron microscopy (SEM), X-ray diffraction technology (XRD), Fourier transform infrared spectroscopy (FT-IR), full-automatic specific surface area and pore size tester (BET), thermogravimetric analyzer (TGA), etc.

[0048] The XRD patterns of sediment-based MOFs are shown in Figure 2. Figure 1 As shown, the XRD spectrum shows that the product mainly has characteristic peaks at 2θ=5.26, 5.94, 6.3, 6.86, 7.16, 10.34, and 11.1°, which are basically consistent with the characteristic peaks of the single crystal simulated XRD spectrum of MIL-100 (Fe) (CCDC no. 640536, CSD-Refcode CIGXIA) and MIL-100 (Al) (CCDC no. 789872, CSD-Refcode BUSPIP), indicating that Example 1 successfully synthesized the sediment-based MOFs.

[0049] The results of scanning electron microscopy are as follows Figure 2 As shown, it can be seen that the sample is in the form of polyhedral particles with a relatively regular shape and uniform size. Most of the particles have a diameter between 0.1 and 0.5 μm. In order to further study the structure and composition of the product, SEM, EDS and TEM-Mapping were used to characterize its element content and element distribution. Figure 2 As shown in the figure, in addition to C and O elements, the product mainly contains Fe and Al elements, accounting for 28.08% and 14.78% of the atomic number, respectively, which further confirms the existence of Fe and Al elements in the product. Figure 2c~g) show that these two elements are evenly distributed in the product. At the same time, the synthesized sediment-based MOFs also contain a small amount of other metal components in the sediment, such as Mg, etc. Other elements may exist in the material in the form of oxides, which is beneficial to improve the catalytic performance of the material.

[0050] The infrared spectrum of the product is as follows Figure 3 Shown: 3418cm -1 The broad peaks nearby belong to the water molecules adsorbed by the product and the vibration peaks of -OH in the organic ligand. 2000~600cm -1 The specific area of ​​1500-1000 cm -1 The absorption peaks appearing between 1640cm and 1640cm are usually considered to be due to the vibration of organic ligands in the MOFs framework. -1 and 1111cm -1 The two absorption peaks appearing at 765cm -1 The absorption peaks at 1450cm correspond to the out-of-plane bending vibration of the CH bond on the benzene ring of the organic ligand. These absorption peaks indicate that there are benzene ring structures and carboxylic acid ligands in the obtained framework structure, which can confirm that trimesic acid has entered the product; -1 The peak at 1381 cm-1 corresponds to the bending vibration of -OH. -1 The strong absorption peaks at 712 and 535 cm correspond to the bending vibration of Fe-OH bonds. -1 The two absorption peaks correspond to the stretching vibration of the Fe-O bond, which confirms the presence of Fe in the product and the formation of Fe-oxo clusters between the inorganic metal Fe(III) atom and the carboxyl group. -1 The absorption peak nearby is related to the bending vibration of the Al-O bond. Combined with the above analysis results, it can be confirmed that Fe / Al-MOFs were successfully synthesized.

[0051] BET analysis in the SEM image was used to detect the porosity of the sample. The N2 adsorption / desorption isotherms and pore size distribution of the sediment-based MOFs were shown in Figure 2. Figure 4 As shown: The adsorption / desorption isotherms of the sediment-based MOFs are type IV isotherms, and an H4-type hysteresis loop appears when P / P0>0.45. The MOFs synthesized on the surface are mesoporous materials, and the pore size distribution diagram ( Figure 4 b) The product contains a large number of mesoporous structures, and the BET surface area of ​​the product reaches 1519.3 m 2 / g, and the total pore volume is 1.1429cm 3 / g, and the average pore size is 3.0091nm (Table 1), indicating that there are abundant mesoporous structures on the sediment-based MOFs, which give them a large specific surface area and total pore volume.

[0052] Table 2 Specific surface area, total pore volume and average pore size of sediment-based MOFs

[0053]

[0054] The thermal stability of the product was determined by thermogravimetric-differential scanning calorimetry. Figure 5 The TGA weight loss curve of the product shows that the sediment-based MOFs experienced two significant weight loss phenomena in the range of 30-800°C. The first weight loss occurred between 30 and 150°C, mainly due to the loss of free water molecules in the pores of MOFs, while the second weight loss in the range of 400-550°C was related to the decomposition of H3BTC and the destruction of the MOFs framework. Although the mass of the product was lost under high temperature, the skeleton structure of the sediment-based MOFs remained stable at 350°C, indicating that the sediment-based MOFs had good thermal stability.

[0055] Example 3 Performance of sediment-based MOFs in catalytic degradation of aquatic organic matter

[0056] Typical organic matter tetracycline was used to study the performance of sediment-based MOFs in activating persulfate to degrade organic matter. Analytical pure tetracycline hydrochloride was dissolved in deionized water to simulate tetracycline wastewater. 50mL of simulated tetracycline wastewater and 50mL of PDS (potassium dodecyl sulfate) solution with a concentration of 0.25mmol / L were taken into a 250mL conical flask, and a certain mass of sediment-based MOFs prepared in Example 1 was added as a catalyst. At a certain pH, 180r / min, 25°C, and no light were shaken, and samples were taken at intervals of 10min. The water samples were filtered through a 0.45μm PTFE water filter head, and the tetracycline concentration was determined at 357nm by ultraviolet spectrophotometry.

[0057] First, the effect of initial pH on the degradation of tetracycline by sediment-based MOFs was investigated. The experimental conditions were: initial tetracycline concentration C0 = 25 mg / L, PDS concentration was 0.25 mmol / L, and MOFs dosage was 0.5 g / L. The degradation effect of tetracycline in the solution was investigated in the range of initial pH of 2.0 to 12.0. Figure 6It can be seen that the degradation effect of tetracycline is significantly related to the solution pH. When pH = 4.0, the tetracycline removal rate is the highest, reaching 74.2%. Then, as the pH increases from 4.0 to 10.0, the tetracycline removal rate gradually decreases, but the decrease is small, and the removal rate remains above 65%, indicating that in this system, tetracycline can be decomposed in a relatively wide pH range (4.0-10.0), and a lower pH value is conducive to the degradation of tetracycline. However, when the pH continues to increase to 12.0, the tetracycline removal rate decreases significantly, only 35.1%. When pH = 2.0, the situation is quite special. The tetracycline concentration in the solution first decreases significantly, then increases slightly, and then continues to decrease. The final tetracycline removal rate is 33.1%. This situation may be related to the adsorption of tetracycline by sediment-based MOFs and the structural destruction of the catalyst under strong acidic conditions. Sediment-based MOFs are materials with rich mesoporous structures and huge specific surface areas. At the same time, due to the hydrogen bonding between MOFs and tetracycline, they have a certain adsorption capacity for tetracycline. In the initial stage of the reaction, while tetracycline is oxidized by persulfate, a small amount of tetracycline is adsorbed on the surface or pore structure of sediment-based MOFs, which reduces the concentration of tetracycline in the solution (e.g. Figure 6 shown).

[0058] Secondly, the effect of the dosage of sediment-based MOFs was investigated. The experimental conditions were: pH = 4.0, C0 = 25 mg / L, PDS concentration was 0.25 mmol / L, and the dosage of sediment-based MOFs was 0.1 g / L, 0.25 g / L, 0.5 g / L, 1 g / L, and 1.5 g / L, respectively. The dosage of sediment-based MOFs increased from 0.1 g / L to 1.5 g / L, and the degradation results of tetracycline were as follows: Figure 7 When the concentration of sediment-based MOFs was 0.1 g / L, the tetracycline removal rate was only 45.7%. As the dosage increased from 0.1 g / L to 1 g / L, the tetracycline removal rate also increased, reaching 85.1%. It can be seen that sediment-based MOFs have good performance in activating persulfate to degrade tetracycline.

[0059] Finally, the effect of persulfate concentration on the performance of sediment-based MOFs in catalyzing persulfate oxidation of tetracycline was investigated. The experimental conditions were: pH = 4.0, C0 = 25 mg / L, and MOFs dosage of 0.5 g / L. Figure 8As shown. When the PDS concentration is gradually increased from 0.1mmol / L to 1.5mmol / L, the tetracycline removal rate in the system also gradually increases, from the initial 59.4% to 75.8%, indicating that the tetracycline removal effect is restricted by the PDS concentration. However, it is worth noting that although the removal rate is constantly increasing, the increase is getting smaller and smaller. When the PDS concentration increases from 0.1mmol / L to 0.5mmol / L, the tetracycline removal rate increases by 11.7%. However, when it continues to increase from 0.5mmol / L to 1.5mmol / L, the removal rate only increases by 4.7%, indicating that the PDS concentration in the system has basically reached saturation. Fe(III) in sediment-based MOFs can react with persulfate to produce SO4· - , SO4· - It plays a role in degrading tetracycline. Therefore, increasing the PDS concentration can provide more persulfate ions to be activated by the catalyst. On the other hand, PDS can release a large amount of H + To lower the pH of the solution, accelerate the release of Fe(III) from MOFs, and generate more SO4 with persulfate. - To improve the removal rate of tetracycline.

[0060] Example 4 Stability evaluation of sediment-based MOFs

[0061] Generally speaking, considering the economic rationality of the catalyst, reusability and structural stability are important factors in evaluating the quality of the catalyst. Therefore, the reusability of the sediment-based MOFs was investigated through three cyclic catalytic experiments. The repeatability test method is as follows: the used sediment-based MOFs were filtered out, washed with anhydrous ethanol and deionized water for 20 minutes in a water bath at 80°C, and then dried in a vacuum drying oven at 60°C for 12 hours, and then used in the tetracycline degradation experiment under the same conditions as in Example 3, and this cycle was repeated three times. The results are as follows: Fig. 9 As shown, within three cycles, the removal rate of tetracycline decreased slightly, from 81.4% in the first cycle to 76.2% after three cycles, and still maintained a high removal rate, indicating that sediment-based MOFs have good reusability in continuous catalytic oxidation experiments.

[0062] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. Application of sediment-based MOFs in the treatment of organic wastewater by activating persulfate, characterized in that: The preparation method of the sediment-based MOFs comprises the following steps: (1) Treat the sludge with acid and centrifuge to separate the supernatant and sediment; (2) Adding a template to the supernatant obtained by centrifugation, heating the supernatant for reaction, purifying, washing, and drying to obtain the sediment-based MOFs; The bottom sludge in step (1) is river bottom sludge; The sludge in step (1) is sludge that has passed through a 100-mesh sieve; The acid in step (1) is hydrochloric acid; The treatment in step (1) is shaking at 35°C and 150 r / min for 2 h; The centrifugation condition in step (1) is 5000 r / min for 10 min; The template agent in step (2) is trimesic acid; The amount of the template added in step (2) is determined by the sum of the molar amounts of Al and Fe in the supernatant: the molar amount of the template = 3:2; The heating reaction in step (2) is carried out at 150° C. for 15 hours; The purification in step (2) is to remove the template by washing with N,N-dimethylformamide, ethanol and water respectively; The drying in step (2) is vacuum drying; The washing in step (2) is washing with anhydrous ethanol and deionized water; The organic sewage is sewage containing tetracycline; the pH value of the organic sewage is 4-10.

Citation Information

Patent Citations

  • Preparation and application of bimetal MOFs (metal-organic frameworks) material

    CN110591108A

  • Method for preparing M<2+>-Al<3+>-Fe<3+> hydrotalcite-like material from water supply sludge and application of M<2+>-Al<3+>-Fe<3+> hydrotalcite-like material

    CN110817970A